Being on Sick Leave: Possible Explanations for Differences of Sick-leave Days Across Countries Privatization - Rigmar Osterkamp; Oliver Röhn (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2005)
Sick-leave days differ widely among industrialised countries. For the US it is 5, for Sweden 20 and for Poland 26 days per year and per employee. The possible causes for these differences have apparently not been systematically analysed. Two groups of contributing factors are considered: (1) natural causes, like the general health situation, employment of women and older persons, and (2) behavioural reactions (a) to macroeconomic conditions,like unemployment or the possibility to work outside the official labour market, and (b) to the design of institutions, like the generosity of granting sick leave. On the basis of 20 countries it is econometrically shown that the main explanatory factors are: generosity of granting sick leave, opportunity costs due to income differentials with neighbouring states, and employment of older people. The unemployment rate contrary to the result of some single-country studies and the employment of women do not contribute to theexplanation of sick-leave differences between countries.
Keywords: I12; I18; 330